Electrochemical generation and observation by magnetic resonance of superparamagnetic cobalt nanoparticles. (10th January 2018) - Khusnuriyalova, Aliya F.; Petr, Andreas; Gubaidullin, Aidar T.; Sukhov, Aleksandr V.; Morozov, Vladimir I.; Büchner, Bernd; Kataev, Vladislav; Sinyashin, Oleg G.; Yakhvarov, Dmitry G.
Abstract: The electrochemical reduction of cobalt dibromide 2, 2′-bipyridine (bpy) complexes (Co/bpy molar ratio 1:1) results in the formation of cobalt nanoparticles (CoNP) formed by the disproportionation reaction of the electrochemically generated cobalt(I) mononuclear complexes. The process of the electrochemical generation of CoNP was monitored by in situ EPR-spectroelectrochemistry where the signals of the ferromagnetic resonance (FMR) have been observed for these species. According to small-angle X-ray scattering (SAXS) analysis the average diameter and the average length of the formed cylindrical CoNP is varied from 9 to 10 nm and 30–32 nm, respectively, and correlates to the g-value and the broadness of the FMR signal observed by in situ EPR-spectroelectrochemistry during electrochemical process. Graphical abstract: Highlights: The electrochemical reduction of the ligand unsaturated cobalt dibromide 2, 2′-bipyridine complexes results in the formation of cobalt nanoparticles (CoNP). The process of the electrochemical generation of CoNP was monitored by in situ EPR-spectroelectrochemistry. The size of the electrochemically generated CoNP was determined by small-angle X-ray scattering (SAXS) analysis.